Reference network benchmarking methodology for performance-based regulation of electric power distribution utility - Cruz, Ivan Benedict Nilo C. (2009)
The global trend of power industry restructuring is creating competitive markets in power generation and supply. Restructuring requires a regulatory methodology that would serve as imitative substitute to competition for the natural monopoly business in transmission and distribution. The performance-based regulation (PBR) of electric utilities are now replacing traditional cost-of-service (COS) regulation. PBR requires that the allowed costs, which utilities can recover from customers, must correspond to the cost of the Reference Network - the efficient network that a competitor, if there is competition, would build and operate to meet the customer demand according to service quality or performance standards. Hence, there is a need to develop analytical models and methodology that can determine such a network. This research determined the Reference Network for selected networks of a Distribution Utility in the Philippines based on the incremental planning approach. To reduce the number of networks to be optimized and analyzed, we used the k-Means Clustering Algorithm to determine the representative LV networks. We optimized the sizes of the conductor and distribution transformer, and the number and locations of sectionalizing devices. Finally, we determined the reasonable power quality, reliability, and technical loss targets, and the reasonable amount for the CAPEX requirement.
"May 2009"
Thesis (M.S. Electrical Engineering) -- University of the Philippines Diliman.
Keywords: Electric power distribution -- Philippines; Electric utilities -- Philippines; Performance-based regulation [electric utilities].